THE INTER-RELIGIOUS TOLERANCE OF THE ALBANIAN MULTI-RELIGIOUS SOCIETY. FACTS AND MISCONCEPTIONS - Gjuraj, Tonin (European Scientific Journal, ESJ, 2013)
Every society seems to have some form of religion. This is one of the ways in which societies differ from each other. The division of society into distinct religious groups is characteristic of Albania, with some of the groups larger than others. Continuous foreign interventions and complete isolation for almost fifty years made Albanians preserve their value system nearly unchanged for several centuries until the present day. The basic principle of this rigid social organization, that is, the kinship system, has always been very strong. Their own social and family structure remained almost the same, and characterized by ancient habits and customs. This social system was basically a patriarchal one, although in southern Albania it was more flexible. The Catholic and Moslem Highlanders lived in the same tribal society and their everyday activities were regulated by customary law. Their reaction to the tradition of Albanian culture was not based on religious distinctions, but on the predominant patriotic feeling. This sort of social organization had some strong requirements such as: honor, the pledged word (bessa), faith, and loyalty. These were permanently supported and clearly identified within the Albanian tribes and family. Regardless of the existence of three different religious groups; Moslems, Orthodox, and Catholics, Albania is a multi-religious society that enjoys inter-religious harmony. Throughout its recorded history, this country has never experienced religious conflicts.